新學制推行以來香港數學教育的發展與挑戰 The Development and Challenges of Mathematics Education in Hong Kong since the New Academic Structure - 張僑平 Qiao-Ping Zhang (Higher Education Foundation, 2021)
自2009年開始香港教育當局推行新的中學學制，學校課程的核心科目和內容，以及相應的升學考試都發生了改變。在十年的發展歷程中，伴隨著數位學習、STEM教育等議題在學校大力推行，香港的數學教育出現了不少的新變化，同時也面對世界其他地區推行素養為本的教育改革影響。本文透過回顧新學制推行以來香港數學教育的發展變化，評析數學課程實施中出現的問題和挑戰。本文發現香港數學新課程面對的問題是新舊並存，主要體現在照顧學習差異、延伸數學課程的學習、數學與STEM教育、中小學課程銜接、新式教學方法和策略、共通能力和數學 素養的關係等方面。更新的課程內容已成既定事實，教師和教師教育者更需要以學養教師的心態反思經驗，發展自身的專業性，為下一輪課程改革做好準備。 Since 2009, the Hong Kong Education Bureau has introduced a new academic structure for secondary education. The core subjects and contents in the school curriculum have been changed, and so did the public entrance examination. Within this decade, with the promotion of hot topics such as e-Learning and STEM education, the mathematics education in Hong Kong has undergone many changes, and in the meanwhile facing the influence of competency-based education reforms around the world. This paper aims to review the recent development of mathematics curriculum since the implementation of the new academic system in Hong Kong. The review finds that the old and new problems coexisted in the implementation of the new mathematics curriculum, which are mainly reflected in individual learning differences, the extended mathematics courses, the role of mathematics in STEM education, the transition from primary to secondary curriculum, the emerging teaching methods/strategies, and the relationship between generic skills and mathematical competency. The updated curriculum has become a fact. These require teachers and teacher educators to reflect on the past experiences, and with the attitude of a scholar-teacher, to develop their professionalism and prepare for the next round of curriculum reform.